2014
DOI: 10.1007/s11154-014-9294-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and lifestyle modification

Abstract: A clustering of metabolic abnormalities such as dyslipidemia, hypertension, and diabetes mellitus, all of which are major risk factors for cardiovascular disease (CVD), occurs more often than by chance. Numerous epidemiological studies, as well as basic researches, have revealed that visceral fat accumulation is closely involved in this risk clustering. This morbid condition is now well recognized as the metabolic syndrome. The concept of the metabolic syndrome, i.e., the involvement of visceral adiposity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 106 publications
0
35
0
3
Order By: Relevance
“…3 4 In addition to genetic features, obesogenic lifestyle defined by unhealthy diet and physical inactivity increase the risk for MeS. [5][6][7][8][9] The prevalence of MeS is increasing worldwide, along with the obesity epidemic and population ageing. 10 11 Estimates of MeS prevalence vary between 15% and 34% in adult populations, [12][13][14][15] and around 8-19% in reproductive-aged women in industrial countries.…”
Section: Introductionmentioning
confidence: 99%
“…3 4 In addition to genetic features, obesogenic lifestyle defined by unhealthy diet and physical inactivity increase the risk for MeS. [5][6][7][8][9] The prevalence of MeS is increasing worldwide, along with the obesity epidemic and population ageing. 10 11 Estimates of MeS prevalence vary between 15% and 34% in adult populations, [12][13][14][15] and around 8-19% in reproductive-aged women in industrial countries.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the pathological mechanism of obesity leading to epidural fat deposition may be the disorder of glucose and lipid metabolism rstly. Based on the close relationship between visceral fat accumulation and abnormal lipid metabolism [29][30][31], it is speculated that SEL may be another site of systemic fat accumulation caused by abnormal lipid metabolism; Secondly, high BMI and obesity are considered as a chronic in ammatory state, which may be one of the causes of excessive growth of adipose tissue in the spinal canal. Hypertrophic adipocytes continued to express pro-in ammatory cytokines, tumor necrosis factor TNFα, interleukin-1β, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Health-related lifestyle can be a very effective strategy that is being used mainly in the prevention of chronic degenerative diseases [4]. Some studies have already shown positive associations between health-related lifestyle and components of metabolic syndrome improvement: systemic arterial blood, hypertriglyceridemia, high blood glucose and HDL-c reductions [5,6] in a study followed for a mean of 3.2 years after random assignment to intensive lifestyle intervention, metformin therapy, or placebo the incidence of the metabolic syndrome was reduced by 41% in the lifestyle group (p < 0.001) and by 17% in the metformin group (p = 0.03) compared with placebo [6]. In addition, cardiac rehabilitation programs are considered good strategies for overall survival; it includes physical training, eating habits reeducation, smoke cessation and stress management [7].…”
Section: Open Accessmentioning
confidence: 99%